The Integration of Zakat Institutions and National Macroeconomic Policies - Fauqah Nuri Aini; Nanda Suryadi; Raja Sakti Putra Harahap (Journal of Innovative and Creativity, 2025)
This study aims to analyze the integration between zakat institutions and national macroeconomic policies as an effort to strengthen the Islamic public finance system in Indonesia. Zakat holds a strategic role not only as a social worship but also as an economic instrument that can support fiscal and monetary policies in achieving public welfare. Using a qualitative descriptive approach through library research, this study examines various academic literatures, government regulations, and reports from national zakat institutions. The findings show that integrating zakat into macroeconomic policy can enhance income redistribution effectiveness, expand the government’s fiscal space, and strengthen national economic resilience. Zakat can also function as an automatic stabilizer to reduce social inequality and maintain economic balance. However, the implementation still faces several challenges, including institutional fragmentation, regulatory limitations, and transparency issues in management. This research concludes that the integration of zakat and national macroeconomic policy requires cross-institutional synergy, regulatory strengthening, zakat system digitalization, and government commitment to position zakat as part of a just and sustainable public policy aligned with the principles of maqashid al-shariah.